MENINGKATKAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN QUANTUM LEARNING MATA PELAJARAN IPA SUB THEMA 1 BAGIAN-BAGIAN TUMBUHAN DI KELAS IV SD NEGERI 040463 KABANJAHE TAHUN PELAJARAN 2021/2022 - Pelista Br Karo Sekal; Wisno Saputra Sembiring Depari; Yuvita Sri Rejeki Br Tarigan (Universitas Negeri Medan, 2022)
Abstract: Improving Student's Learning Outcomes Using Quantum Learning Learning Model Ipa Lesson Sub Thema 1 Plants Parts in Class Iv Sd Negeri 040463 Kabanjahe Academic Year 2021/2022. The research carried out is classroom action research with the aim of knowing the implementation of learning, knowing mastery of learning and to determine the improvement of student learning outcomes. The subjects of this study were 25 people in class V and the object of this research was using the Quantum Learning Model. The instruments used were observation sheets and multiple choice tests. Based on the results of this study, it was found that the implementation of learning on teacher activities was 83% very good, the implementation of student activities scored 88 good criteria while classical completeness was 92% and increased learning outcomes 5%. Thus, this research can be concluded that, the implementation of learning criteria is good, student learning outcomes are completed and improved classically using the Quantum Learning Model for Science Subject Class V SD Negeri 040463 in Kabanjahe Academic Year 2021/2022